Carbon materials for high volumetric performance supercapacitors: design, progress, challenges and opportunities. Issue 3 (21st December 2015) - Wang, Qian; Yan, Jun; Fan, Zhuangjun
Abstract : This review summarizes recent progress in the design and fabrication of carbon materials for high volumetric performance supercapacitors. Abstract : Volumetric performance, a much more reliable and precise parameter for evaluating the charge-storage capacity of supercapacitors compared with gravimetric performance, has aroused more and more interest in recent years owing to the rapid development of miniaturized, portable and wearable electronic devices as well as electric vehicles. Various carbon materials are widely used as electrode materials in supercapacitors. However, their intrinsically low specific capacitance and relatively low bulk density lead to a relatively low volumetric performance, significantly limiting their future application. This critical review points out the crucial importance of volumetric performance and reviews recent achievements of high volumetric performances obtained through the rational design and development of novel carbon-based materials. Particular emphasis is focused on discussing the factors influencing the volumetric performance of carbon materials from a structural design point of view. We then make an in-depth summary of various promising approaches used to make significant research breakthroughs in recent years. Current challenges, future research directions and opportunities in this fascinating field of supercapacitors with high gravimetric and volumetric performances are also discussed.